Utilization of IoT and GIS` for Pest Monitoring and Identification to Enhance Sweet Potato Production in Dryland - Qurnain, Muhammad Zul; Noviandi Guna, Barito; Irawan, Erwin; Mulyati (Unram Journal of Community Service, 2025)
Sweet potato (Ipomoea batatas) is an important food crop with significant economic and social value, particularly in tropical regions. However, its productivity is often affected by pest attacks, which are frequently not detected early due to the limitations of traditional monitoring systems. This study aims to develop a pest monitoring system for sweet potatoes by utilizing Internet of Things (IoT) technology and Geographic Information Systems (GIS). IoT enables real-time monitoring of environmental conditions such as temperature, humidity, and light, while GIS is used to map the spatial distribution of pests. By integrating these two technologies, pest control can be carried out more efficiently, accurately, and environmentally friendly. This system provides early notifications to farmers regarding pest infestations, allowing for quick and effective decision-making in pest management. Additionally, the use of IoTand GIS isexpected to reduce excessive pesticide use andenhance the sustainability of sweet potato production. This article offers an innovative solution for pest management based on spatial-temporal data in dryland agroecosystems.